Sharing One's Fortune? An Experimental Study on Earned Income and Giving - Mirco Tonin; Michael Vlassopoulos (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper we investigate the relationship between earnings and charitable giving. We set up a real effort experiment, in which subjects enter data in four one-hour occasions and are paid a piece rate. From the second occasion onwards, we randomly assign half of the subjects to a treatment with higher piece rates. At the end we ask subjects whether they want to donate a share of their earnings to a charity of their choice. We find that, despite large differences in earnings due to the different piece rates, subjects receiving the higher piece rate are actually less likely to give, and that givers in the two groups give the same share of their total earnings. Charities receive the same average donation from members of the two groups indicating that subjects in this experiment do not treat charitable giving as a normal good.
Keywords: D64; J39; 330; charity; earnings; buck; effort; windfall